First international consensus conference on standardization of oncoplastic breast conserving surgery - Weber, Walter P.; Soysal, Savas D.; Heil, Jörg (Breast cancer research and treatment, 2017)
PurposeTo obtain consensus recommendations for the standardization of oncoplastic breast conserving surgery (OPS) from an international panel of experts in breast surgery including delegates from the German, Austrian and Swiss societies of senology.MethodsA total of 52 questions were addressed by electronic voting. The panel’s recommendations were put into context with current evidence and the report was circled in an iterative open email process until consensus was obtained.ResultsThe panelists considered OPS safe and effective for improving aesthetic outcomes and broadening the indication for breast conserving surgery (BCS) towards larger tumors. A slim majority believed that OPS reduces the rate of positive margins; however, there was consensus that OPS is associated with an increased risk of complications compared to conventional BCS. The panel strongly endorsed patient-reported outcomes measurement, and recommended selected scales of the Breast-Q™-Breast Conserving Therapy Module for that purpose. The Clough bi-level classification was recommended for standard use in clinical practice for indicating, planning and performing OPS, and the Hoffmann classification for surgical reports and billing purposes. Mastopexy and reduction mammoplasty were the only two recognized OPS procedure categories supported by a majority of the panel. Finally, the experts unanimously supported the statement that every OPS procedure should be tailored to each individual patient.ConclusionsWhen implemented into clinical practice, the panel recommendations may improve safety and effectiveness of OPS. The attendees agreed that there is a need for prospective multicenter studies to optimize patient selection and for standardized criteria to qualify and accredit OPS training centers.
Gesehen am 04.04.2019